2009
DOI: 10.1037/a0017749
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating emotion-induced blindness and hypervision.

Abstract: Previous findings suggest that emotional stimuli sometimes improve (emotion-induced hypervision) and sometimes impair (emotion-induced blindness) the visual perception of subsequent neutral stimuli. We hypothesized that these differential carryover effects might be due to 2 distinct emotional influences in visual processing. On the one hand, emotional stimuli trigger a general enhancement in the efficiency of visual processing that can carry over onto other stimuli. On the other hand, emotional stimuli benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
87
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 68 publications
11
87
4
Order By: Relevance
“…Once an emotional stimulus is presented, it changes the way subsequently presented neutral objects compete for attention. For example, the ability to detect a solitary neutral stimulus can be enhanced by presenting an emotionally arousing stimulus just beforehand (Bocanegra & Zeelenberg, 2009; Padmala & Pessoa, 2008; Zeelenberg & Bocanegra, 2010), at least if the stimulus has low spatial frequency (Lee, Baek, Lu, & Mather, in press). Moreover, the presentation of an emotional stimulus has also been shown to enhance the ability to identify a neutral target within an array of neutral distracters (Becker, 2009; Olatunji, Ciesielski, Armstrong, & Zald, 2011; Phelps, Ling, & Carrasco, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Once an emotional stimulus is presented, it changes the way subsequently presented neutral objects compete for attention. For example, the ability to detect a solitary neutral stimulus can be enhanced by presenting an emotionally arousing stimulus just beforehand (Bocanegra & Zeelenberg, 2009; Padmala & Pessoa, 2008; Zeelenberg & Bocanegra, 2010), at least if the stimulus has low spatial frequency (Lee, Baek, Lu, & Mather, in press). Moreover, the presentation of an emotional stimulus has also been shown to enhance the ability to identify a neutral target within an array of neutral distracters (Becker, 2009; Olatunji, Ciesielski, Armstrong, & Zald, 2011; Phelps, Ling, & Carrasco, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have accounted for findings of different effects of arousal on low-versus high-spatial-frequency stimuli by arguing that the amygdala responds to emotional arousal by potentiating magnocellular-type channels in the visual system while suppressing parvocellular-type channels (Bocanegra & Zeelenberg, 2009b, 2011a; Borst & Kosslyn, 2010). This bias favoring magnocellular-type channels should preferentially enhance processing of low-spatial-frequency information because magnocellular cells within the lateral geniculate nucleus of the thalamus have a lower spatial resolution than parvocellular cells (Sincich & Horton, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Ciesielski, Armstrong, Zald, and Olatunji (2010) reported that the enhanced attentional blink effect for emotional stimuli rapidly declined from short (200 ms) to longer time lags (400 ms and 600 ms) and even reversed for the longest time lag of 800 ms (i.e., enhanced instead of diminished target processing following negative images). Bocanegra and Zeelenberg (2009) also demonstrated that negative word cues impaired subsequent target identification at short (50 and 500 ms) inter stimulus intervals (ISIs), but improved target identification at a longer ISI of 1000 ms. Together, these results suggest that primary task performance deteriorates only, or foremost, when emotional distracters and task-relevant targets are presented in close temporal proximity.…”
mentioning
confidence: 98%